Income Inequality, Mobility and Economic Insecurity in Australia - Tang, K; Rohde, N; Rao, P (My University, 2009)
In this paper we analyze income inequality and mobility using the first six waves of the HILDA (Household Income and Labour Dynamics in Australia) panel survey. The mobility of Australian incomes is measured and our evidence suggests that domestic wages and salaries are slightly less mobile than incomes in some other developed countries. This mobility is investigated in greater detail and it is found that much of the intertemporal variation occurs in the middle and lower end of the income distribution. Lastly we recognize that the mobility of an individual’s income may be used as a measure of economic insecurity and we present measures of permanent income inequality that account for this phenomenon. We find that permanent income inequality increases substantially when adjustments to account for aversion to volatility are performed.
University of Queensland Discussion Papers
Keywords: Finance -- Income (Salary and Wages); Finance; Income, wealth and finances; Income, wealth and finances